Global development of organic agriculture: challenges and prospects - Halberg, N.; Alr<o>e, H. F.; Alr<o>e, H. F.; Halberg, N.; Knudsen, M. T.; Knudsen, M. T.; Kristensen, E. S.; Kristensen, E. S. (Wallingford :CABI Publishing, 2006)
This book provides an overview of the potential role of organic agriculture in a global perspective. Initially, the book provides a description of global trends in agriculture followed by discussions on sustainability, globalization and the relatively new concepts of 'ecological justice' and 'political ecology'. Different views on economy and trade are discussed with a focus on ecological economics. Then, the status and possibilities of organic agriculture in developing countries are discussed, including problems of nutrient cycles and soil depletion plus issues on veterinary medicine. Furthermore, organic farming is related to the world food supply. The possibilities of knowledge exchange in organic agriculture are also evaluated and how a large-scale conversion to organic agriculture would impact on food security. Finally, prospects and challenges of organic farming in a globalized world are discussed in a synthesis chapter. This book will be of interest to researchers in organic agriculture, agricultural economics and rural development as well as NGO workers and policy makers. The book has 12 chapters and a subject index.
Keywords: EE110 - Agricultural Economics; EE115 - Natural Resource Economics, (New March 2000); EE116 - Food Economics, (New March 2000); EE600 - International Trade; FF150 - Plant Cropping Systems; JJ600 - Soil Fertility; LL180 - Animal Husbandry and Production, (New March 2000); LL800 - Animal Health and Hygiene (General); UU485 - Social Psychology and Social Anthropology, (New March 2000); Developing Countries